Streets, churches and squares: The spaces of andean theatrical manifestations (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The purpose of this text is to present and describe the use and functions of the spaces in which Andean theatrical manifestations take place. We conceive Andean theatrical manifestations as those dances that form part of the rituals and festivals developed in the Andes. This description is presented in light of the continuum (Schechner) and liminality (Dieguez) concepts, and comes mainly from my own experience as a participant in the Virgen del Carmen festival in Paucartambo (Cusco, Peru) and a colaborator of a dance troupe at the Feast of the Virgin of Cocharcas in Sapallanga (Junín, Peru).
Keywords: Andean theatricality; Scenic space; Ritual; Performance